Uji Efek Ekstrak Etanol 96% Anggur Merah (Vitis Vinifera) Terhadap Penurunan Kadar Kolesterol Pada Tikus Putih (Rattus Novergicus) Yang Diberi Pakan Hiperkolesterolemia Dan Diinduksi Triton X-100 - Yusmadri, Riyan (2016)
THE EFFECT OF 96% ETHANOL EXTRACT OF RED GRAPE (Vitis Vinifera) ON REDUCING CHOLESTEROL LEVELS IN WHITE RATS (Rattus Novergicus) SUPPLEMENTED WITH HYPERCHOLESTEROLEMIA FOODS AND INDUCED BY TRITON X-100 Riyan yusmadri1, EM Sutrisna2, Nurhayani2 Faculty of Medicine, Muhammadiyah Surakarta University Background : Red grape contains pterostilbine, reservatrol, proantocianidine and lycopene which have an effect on reducing cholesterol levels. Objective : To determine the effect of 96% ethanol extract of red grape (Vitis vinifera) on reducing blood cholesterol levels. Methods : This study was a laboratorium experimental study with a pre and post test with control group design. The subjects were 25 male white rats (Rattus novergicus), body weight 150-200 grams, aged 3-4 months, and divided into 5 groups with simple random sampling. The groups were negative control (aquadest), positive control (simvastatin 0,2 mg/200 gram BW/day), dose I (100 mg/200 gram BW/day), dose II (250 mg/200 gram BW/day) and dose III (500 mg/200 gram BW/day). Cholesterol levels were measured before and after applying treatment. This study was held for 10 days and date were analyzed with paired t-test and one way ANOVA test followed by Post Hoc test. Results : The 96% ethanol extract of red grape dose I (100 mg/200 gram BW/day), dose II (250 mg/200 gram BW/day) and dose III (500 mg/200 gram BW/day) are found effective on reducing blood cholesterol levels with a mean reduction of 147,5 mg/dl, 135,2 mg/dl and 97,2 mg/dl, respectively. Statistical analysis using one-way ANOVA showed p value of 0,000 (p<0,05), which determines a significant difference of triglyceride levels among each group. Conclusion: The 96% ethanol extract of red grape dose I, II and III are effective on reducing blood cholesterol levels in white rats (Rattus novergicus). Dose III is found to be the most effective dose in cholesterol reduction.